Differential Host Immune Responses after Infection with Wild-Type or Lab-Attenuated Rabies Viruses in Dogs. - Clement W Gnanadurai; Yang Yang; Ying Huang; Zhenguang Li; Christina M Leyson; Tanya L Cooper; Simon R Platt; Stephen B Harvey; Douglas C Hooper; Milosz Faber; Zhen F Fu (Public Library of Science (PLoS), 2015)
METHODOLOGY/PRINCIPAL FINDINGS:The experimental infection of dogs with TriGAS induced high levels of VNA in the serum, whereas wt RABV infection did not. Dogs infected with TriGAS developed antibodies against the virus including its glycoprotein, whereas dogs infected with DRV-NG11 only developed rabies antibodies that are presumably specific for the nucleoprotein, (N) and not the glycoprotein (G). We show that infection with TriGAS induces early activation of B cells in the draining lymph nodes and persistent activation of DCs and B cells in the blood. On the other hand, infection with DRV-NG11 fails to induce the activation of DCs and B cells and further reduces CD4 T cell production. Further, we show that intrathecal (IT) immunization of TriGAS not only induced high levels of VNA in the serum but also in the CSF while intramuscular (IM) immunization of TriGAS induced VNA only in the serum. In addition, high levels of total protein and WBC were detected in the CSF of IT immunized dogs, indicating the transient enhancement of blood-brain barrier (BBB) permeability, which is relevant to the passage of immune effectors from periphery into the CNS. CONCLUSIONS/SIGNIFICANCE:IM infection of dogs with TriGAS induced the production of serum VNA whereas, IT immunization of TriGAS in dogs induces high levels of VNA in the periphery as well as in the CSF and transiently enhances BBB permeability. In contrast, infection with wt DRV-NG11 resulted in the production of RABV-reactive antibodies but VNA and antibodies specific for G were absent. As a consequence, all of the dogs infected with wt DRV-NG11 succumbed to rabies. Thus the failure to activate protective immunity is one of the important features of RABV pathogenesis in dogs.